Intestinal tuberculosis, a diagnostic challenge: Report of a case - Villamizar Villamizar, Juan Paulo (2016)
Gastrointestinal tuberculosis is a rare and difficult pathology to diagnose, which is associated with various social and economic factors as well as the state of health of the sufferer. This case report was made about intestinal tuberculosis in the Department of Boyacá, in which the main clinical, paraclinical, the process of diagnosis and management plan in place in the patient are described. Gastrointestinal involvement of tuberculosis has a low incidence, being the sixth place of commitment. Signs and symptoms manifested by the patient are not specific and often the health staff suspect and first focuses on other diseases that are more prevalent. From this medical case, the various diagnostic suspicions that were raised in the course of the disease are emphasized in order achieve a diagnosis of the intestinal tuberculosis, which provides a higher guidance for doctors to take this disease into account in their clinical practice.